Association of patient-reported financial barriers with healthcare utilization among Medicare beneficiaries with a history of cancer. Issue 28 (1st October 2022) - Biddell, Caitlin; Spees, Lisa; Trogdon, Justin G.; Kent, Erin E.; Rosenstein, Donald L.; Angove, Rebekah SM; Wheeler, Stephanie B.
Abstract : 220 Background: Cancer survivors are at heightened risk of experiencing financial barriers to healthcare (FBs), which may increase the likelihood of adverse clinical outcomes. We aimed to (1) identify characteristics associated with experiencing FBs, and (2) examine the association of FBs with emergency department (ED) visits and inpatient hospitalizations among US adult cancer survivors enrolled in Medicare. Methods: We used 2011 – 2013 and 2015 – 2017 Medicare Current Beneficiary Survey (MCBS) data, a nationally representative survey, to identify adults with a history of non-skin cancer (N = 4511). We defined FBs as trouble accessing care and/or delayed care due to cost in the prior year. Healthcare utilization is captured in MCBS by reconciling self-reported events and fee-for-service claims. After examining bivariate associations between beneficiary characteristics and FBs, we used propensity-weighted logistic regression to examine associations between FBs and adverse healthcare events (any ED visits, any inpatient hospitalizations) in the year following report of FBs. Results: Overall, 11.8% (95% CI: 10.7% - 13.0%) of adult Medicare beneficiaries with a history of cancer reported FBs in the prior year, with higher burden among beneficiaries less than 65 years of age (35.6% vs. 8.6%, p < 0.0001), with annual income < 25, 000 (19.4% vs. 7.4%, p < 0.0001), and identifying as persons of color (15.7% vs. 11.2%, p = 0.01). Beneficiaries eligible for a Part D low-income subsidy were more likely to report FBs compared to those who were not eligible, with those with eligibility for only part of the year (vs. the full year) reporting the highest prevalence of FBs (36.5% vs. 20.8%, p < 0.0001). The overall prevalence of ED visits and inpatient hospitalization was 18.2% and 18.8%, respectively. In bivariate models, reporting FBs was associated with an 8.1 percentage point (95% CI: 1.7 – 14.5) increase in the probability of ED visits. In propensity-weighted multivariate models, this association was insignificant (0.8; 95% CI: -3.7 – 5.3). The association between FBs and inpatient hospitalization was not significant. Number of chronic conditions was the strongest predictor of utilization, with having 5+ conditions (vs. cancer only) associated with a 21.1 (95% CI: 16.5 – 25.7) and 15.4 (95% CI: 9.2 – 21.7) percentage point increase in the probability of ED visits and inpatient hospitalizations, respectively. Conclusions: Over one in ten Medicare beneficiaries with a history of cancer report trouble accessing care or delayed care for cost-related reasons, with a heightened prevalence among beneficiaries less than 65 and those eligible for a low-income subsidy. Reporting FBs is not associated with increased ED and inpatient utilization. Nevertheless, identifying characteristics associated with FBs among cancer survivors can inform targeted clinic- and policy-level intervention.